IMPLEMENTASI KOMPETENSI GURU DALAM MENDESAIN DAN MELAKSANAAN PEMBELAJARAN TERPADU PADA KTSP DAN KURIKULUM 2013 DI MADRASAH IBTIDAIYAH NEGERI (MIN) TUNGGANGRI KALIDAWIR TULUNGAGUNG - Arif, Moh. (Jurnal Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2015)
The ability of teachers in designing learning becomes one factor in the successful implementation of integrated learning MIN tunggangri, based on the formulation of the problem as follows: 1) How is the competence of teachers in Designing Integrated learning at MIN Tunggangri Kalidawir Tulungagung? 2) What are the factors that affect the competence of teachers in the process pembelajaranTerpadupada SBC and Curriculum 2013 in MIN Tunggangri Kalidawir Tulungagung? And, 3) How is the implementation of teacher competence in Designing and implementing the learning process and curriculum SBC Terpadupada 13 at MIN Tunggangri Kalidawir Tulungagung? Based on the formulation of the problem above, the results showed the following 1) the ability of teachers in designing integrated learning at MIN Tunggangri researchers found as follows, 2) the ability of teachers to design learning has been going well, it is based on educational qualifications and participation in the development of teacher competence in designing integrated learning both in the curriculum system of 2006 (SBC) or curriculum in 2013 which is currently in terapakan and the factors or problems faced by teachers in MIN Tunggangri in designing and implementing the thematic learning according to the curriculum in 2013 are limited facilities and infrastructure, availability of books teachers and students and most teachers have not been S2 even if the educational background S2 not be a mandatory requirement for teachers at level MIN/SD, but according to the headmaster very teacher at MIN Tunggangri always encouraged to improve their competence either seacara academic or non-academic one with proceed to S2. Keywords: Teacher Competences, Design, Integrated Learning, Curriculum 2013